Murine cytomegalovirus infection of cultured mouse embryos. - Tsutsui, Y. (1987)
Isolated mouse whole embryos of 7.5 days' gestation were infected with murine cytomegalovirus (MCMV) and cultured in pure rat serum. Although the MCMV infection had little effect on the survival and development of the embryos during 3 days of cultivation, immunohistochemical analysis of their serial sections using monoclonal antibody showed MCMV-infected cells in various portions of the embryos. This monoclonal antibody, when tested with the use of infected cultured mouse fibroblasts, reacted with nuclear antigen within 2 hours after infection and also reacted with nuclear inclusions in the late phase of infection. The viral antigen-positive cells detected by the monoclonal antibody were present in almost all of the ectoplacental cone and the yolk sac and in about 82% of the embryos. In the embryos, antigen-positive cells were frequently observed in the epithelium of the digestive tracts, endothelial cells of the blood vessels, and the mesodermal cells. In some of the embryos, viral antigen-positive cells were clearly observed in a small percentage of the blood cells. These findings indicate that blood cells, in addition to cell migration during embryogenesis, may play an important role in transmission of infectious virus into the embryos. Mouse whole embryo culture infected with MCMV can provide a model for the study of cellular tropism related to congenital infection by cytomegalovirus.